Kebijakan Zero Draft COC Indonesia Dalam Mediasi Konflik Di Laut Cina Selatan - Aprianto Trianggoro Putro; Endro Legowo; Panji Suwarno; Pujo Widodo; Achmed Sukendro (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This article aims to analyze Indonesia's conflict mediation capabilities in the South China Sea. The problem is focused on Indonesia's Zero Draft Code policy in providing mediation direction through the outline of various draft agreements or agreements or agreements. To approach this problem, references to public policy theory, mediation, conflict and threats are used. The data is collected through official Indonesian government documents related to COC policy in the South China Sea, such as official statements, regulations, decisions, or other related documents. In addition, academic publications such as articles, journals, or research reports discussing Indonesia's COC policy in mediating conflicts in the South China Sea can be a source of relevant data and qualitative analysis. The results and findings in this study explain that the developing conflict has encouraged Indonesia to mediate through negotiation and the formulation of a code of ethics or zero draft code as a reference in encouraging the behavior of each country in conflict. Indonesia has an interest in maintaining regional stability in Southeast Asia. The study concluded that ASEAN member states in conflict with China agreed to the code of conduct, although China has not agreed given the US involvement in the conflict.